Influence of physical activity on resilience in adults with shoulder pain - Zurita Ortega, F.; Espejo Garcés, T.; Cofré Boladós, C.; Martínez Martínez, A.; Castro Sánchez, M-; Chacón Cuberos, R. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
The quality of life of Chilean adult population is increasing, which generates a great interest in the health-educational establishments. This research aims to study the relationship between physical activity and resilience in older adults with pathologies of shoulder. It was conducted a descriptive and cross-sectional study in 41 adults from Santiago of Chile, with an average age of 58.17 years old (SD = 11.754), using as a main instruments the CD-RISC questionnaire and the scale of shoulder’ assessment “UCLA”. Results showed that half of adults do physical activity and that they show an acceptable locus of control and compromise, being spirituality the least scored. Physical activity and gender did not show relations, although the dimensions of resilience with high score were related to sport practice.